P5_PO_90_2023_Braun.pdf - Gill, Philip (Cranfield University, 2023)
Diffusion Coefficient of Nitrocellulose in Propellants S Braun - ISL - French-German Research Institute of Saint-Louis, 9th International Nitrocellulose Symposium - Poster
Keywords: 'nitrocellulose'